Optimalisasi Peran Guru dalam Era Kontemporer: Perspektif Menejemen Dakwah Berdasarkan al-Qur’an Surah Ali Imran [3]: 79 - Yuniarti, Fani Firda (Maddah: Journal of Advanced Da'wah Management Research, 2024)
Amid the noble duties of a teacher, the position of teachers in the education system of this country continues to struggle with various issues, including teacher welfare, the functional status of teachers as temporary staff, and the contractual teaching system that seemingly equates teachers with outsourced labor. Additionally, the government has proposed a policy to sell teachers' services through marketplace platforms. Are teachers' services comparable to commercial goods? Where is the respect for teachers and their duties? This study employs a library research approach. The findings on optimizing the role of teachers from the perspective of the Qur'an, Surah Ali Imran [3]: 79, reveal that the policy of placing teachers on a marketplace does not position teachers as the central figures of education aimed at producing a "rabbani" generation. Instead, it positions teachers merely as service providers and laborers. This policy contradicts the intended meaning of the word "rabbani" associated with both teachers and students. According to this verse, both teachers and students should embody the concept of "rabbani" in their teaching and learning processes. A "rabbani" teacher instructs their students with the aim of developing profound knowledge, while a "rabbani" student respects their teacher through proper conduct and dedication in learning. Selling teachers' services on a marketplace does not provide the space for fostering such "rabbani" teachers and students..